Vascular Normalization by Vascular Endothelial Growth Factor Receptor 2 Blockade Induces a Pressure Gradient Across the Vasculature and Improves Drug Penetration in Tumors - Tong, Ricky T.; Boucher, Yves; Kozin, Sergey V.; Winkler, Frank; Hicklin, Daniel J.; Jain, Rakesh K. (Cancer research (Chicago, Ill.), 2004)
Elevated interstitial fluid pressure, a hallmark of solid tumors, can compromise the delivery of therapeutics to tumors. Here we show that blocking vascular endothelial growth factor (VEGF) signaling by DC101 (a VEGF-receptor-2 antibody) decreases interstitial fluid pressure, not by restoring lymphatic function, but by producing a morphologically and functionally “normalized” vascular network. We demonstrate that the normalization process prunes immature vessels and improves the integrity and function of the remaining vasculature by enhancing the perivascular cell and basement membrane coverage. We also show that DC101 induces a hydrostatic pressure gradient across the vascular wall, which leads to a deeper penetration of molecules into tumors. Thus, vascular normalization may contribute to the improved survival rates in tumor-bearing animals and in colorectal carcinoma patients treated with an anti-VEGF antibody in combination with cytotoxic therapies.